Menuntut Ilmu dalam Perspektif Pendidikan Agama Islam: Analisis terhadap Prinsip-Prinsip Dasar - Devina Devina; Nazuwa Putri Khairunissa; Syamsi Ramadhan; Alihan Satra (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2026)
This article discusses the fundamental principles of seeking knowledge from an Islamic perspective and their application in daily life. In Islam, seeking knowledge is understood not merely as an intellectual activity, but also as a form of worship that encompasses spiritual, moral, and social dimensions. This study employs a library research method with a descriptive-qualitative approach through the analysis of primary and secondary sources, including the Qur’an, hadiths, books, and relevant scientific journals. The findings reveal that the main principles of seeking knowledge include sincere intention, proper manners toward teachers, patience, humility, academic honesty, and the implementation of knowledge in real life. The Qur’an and hadith emphasize that people of knowledge hold a high status in the sight of Allah SWT. Furthermore, Islamic scholars play a strategic role as the heirs of the prophets in preserving the purity of Islamic teachings and guiding the Muslim community. This study also finds that maintaining consistency in seeking knowledge in the modern era faces challenges such as digital distractions, declining motivation, burnout, and weak learning systems. Therefore, an integration of knowledge, morality, and spirituality is necessary so that the knowledge acquired may bring blessings and benefits to individuals and society.